New considerations on the health of the persons with intellectual developmental disorders - Anabel Folch-Mas; María José Cortés-Ruiz; Luis Salvador-Carulla; Natalia Kazah-Soneyra; Marcia Irazábal-Giménez; Silvia Muñoz-Lorente; Javier Tamarit-Cuadrado; Rafael Martínez-Leal (Instituto Nacional de Salud Pública, 2017)
Recent literature indicates that people with Disorders of Intellectual Development (DID) experience health disparities in the pathologies that they present, and a worst access to health care. However, current evidence-based knowledge is still sparse outside the Anglo-Saxon  ountries. The POMONA-I and POMONA-II European projects aimed to collect information on the health status of people with DID in Europe. The POMONA-ESP project in Spain is meant to collect health information in a wide and representative sample of persons with DID. Also, there are studies that claim for the need of specialized services for people with DID at the public health system. There are also studies about the current state of the education and training about DID for students within the health sector. In this paper we review the latest evidences about the health of the persons with DID and we present the main research activities and care initiatives about this issue